Rolul instructiv-educativ al basmului. metode de cercetare [Articol] - Ungureanu, Maria (CEP USM, 2021)
The interest in fairy tale research first animated folklorists. After the emergence of the collection of fairy tales of the Brothers Grimm and the formulation of the first theories about the origin of the fairy tale, this literary-artistic product of popular invoice became the center of inters of researchers in fields such as philosophy, psychology, psychoanalysis, sociology, pedagogy, linguistics, stylistics, literary criticism, etc. The specialized literature therefore includes studies regarding the origin, typology and structure of the fairy tale, the expressive qualities of the popular language present in the fairy tale its historical and sociological role. More recently, it is research that has shown the displays of his educational valences that psychologists and psychoanalysts were very interested in. More recently, there is research aimed at emphasizing its educational values, which were very interested in psychologists and psychoanalysts. Today, pedagogy joins the sciences interested in determining the instructive-educational role of the fairy tale, necessary in re-orinting the education of the present and the future to immutable values and human virtues. Each domain uses specific methods for fairy-tale research.
THE INSTRUCTIVE-EDUCATIONAL ROLE OF THE FAIRY TALE. RESEARCH METHODS
Keywords: education; fairy tale; research; comparative method